2008
DOI: 10.1016/j.schres.2007.12.474
|View full text |Cite
|
Sign up to set email alerts
|

Elevated neuregulin-1 and ErbB4 protein in the prefrontal cortex of schizophrenic patients

Abstract: Neuregulin-1 (NRG1) and its receptor, ErbB4, have been implicated in schizophrenia at both gene and transcript levels. The present investigation compared NRG1 and ErbB4 protein levels in prefrontal cortical (PFC) cytoplasmic and nuclear fractions among normal, schizophrenic, bipolar and major depressed subjects from the Stanley Consortium. We used immunoblotting procedures to examine potential NRG1 and ErbB4 immunoreactive bands, but specifically quantified NRG1 immunoreactive signals at 42, 48 and 53kDa and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
128
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(135 citation statements)
references
References 48 publications
(97 reference statements)
5
128
2
Order By: Relevance
“…However, current results do not support this claim, since the majority of post-mortem studies in schizophrenia have found no correlation between overexpressions of NRG1/ErbB4 and dosages of antipsychotic treatment (Chong et al, 2008;Hahn et al, 2006;Hashimoto et al, 2004;Law et al, 2007;Law et al, 2006). Furthermore, elevated expression of the NRG1 intracellular part was only observed in the PFC of schizophrenia, but not bipolar disorders and depression, although bipolar patients were also exposed to antipsychotics (Chong et al, 2008). Positive associations between intronic SNPs (rs7598440, rs707284, rs839523) and elevated mRNA expressions of ErbB4 isoforms containing a metalloprotease cleavable extracellular domain (JM-a) and CYT-1 domain have been reported, which suggests a splice-variant specific expression of ErbB4 in the brain in schizophrenia (Law et al, 2007).…”
Section: Dysregulated Nrg1-erbb4 Signalling In Schizophrenia: Is It Ccontrasting
confidence: 92%
See 4 more Smart Citations
“…However, current results do not support this claim, since the majority of post-mortem studies in schizophrenia have found no correlation between overexpressions of NRG1/ErbB4 and dosages of antipsychotic treatment (Chong et al, 2008;Hahn et al, 2006;Hashimoto et al, 2004;Law et al, 2007;Law et al, 2006). Furthermore, elevated expression of the NRG1 intracellular part was only observed in the PFC of schizophrenia, but not bipolar disorders and depression, although bipolar patients were also exposed to antipsychotics (Chong et al, 2008). Positive associations between intronic SNPs (rs7598440, rs707284, rs839523) and elevated mRNA expressions of ErbB4 isoforms containing a metalloprotease cleavable extracellular domain (JM-a) and CYT-1 domain have been reported, which suggests a splice-variant specific expression of ErbB4 in the brain in schizophrenia (Law et al, 2007).…”
Section: Dysregulated Nrg1-erbb4 Signalling In Schizophrenia: Is It Ccontrasting
confidence: 92%
“…It should be noted that schizophrenia patients usually have undergone chronic antipsychotic treatments, therefore one key question is whether elevated NRG1-ErbB4 signalling observed in post-mortem studies is caused by antipsychotic treatment. However, current results do not support this claim, since the majority of post-mortem studies in schizophrenia have found no correlation between overexpressions of NRG1/ErbB4 and dosages of antipsychotic treatment (Chong et al, 2008;Hahn et al, 2006;Hashimoto et al, 2004;Law et al, 2007;Law et al, 2006). Furthermore, elevated expression of the NRG1 intracellular part was only observed in the PFC of schizophrenia, but not bipolar disorders and depression, although bipolar patients were also exposed to antipsychotics (Chong et al, 2008).…”
Section: Dysregulated Nrg1-erbb4 Signalling In Schizophrenia: Is It Ccontrasting
confidence: 78%
See 3 more Smart Citations